Vascular Events and Carotid Atherosclerosis: A 5-Year Prospective Cohort Study in Patients with Type 2 Diabetes and a Contemporary Cardiovascular Prevention Treatment. (23rd December 2019) - Vouillarmet, Julien; Marsot, Charlotte; Maucort-Boulch, Delphine; Riche, Benjamin; Helfre, Marjorie; Grange, Claire
Abstract : Background and Aims . European recommendations on cardiovascular prevention suggest that carotid atherosclerosis assessment by duplex ultrasonography could help in some cases to better assess CV risk. We investigated whether the presence of carotid atherosclerosis determined by duplex ultrasonography is associated with cardiovascular events in patients with type 2 diabetes and could therefore help to reclassify cardiovascular risk. Methods . Among 624 consecutive patients with type 2 diabetes and carotid atherosclerosis assessment by duplex ultrasonography between January and December 2012, 583 (93%) were included and followed up prospectively. The primary endpoint was the occurrence of cardiovascular events. The rate of new cardiovascular events was compared between patients with (n = 104 ) and those without (n = 479 ) prior cardiovascular events. Results . A total of new 104 cardiovascular events occurred in 72 patients (12.5%) during a mean ± SD follow-up period of 5.1 ± 1.6 years. At baseline, for 202 patients (34.6%), carotid evaluation was normal; 381 (65.4%) had a carotid atherosclerosis lesion. The presence of carotid atherosclerosis at baseline was not significantly associated with an increased risk of new cardiovascular events in both groups. The rate of new cardiovascular events was more than twice as high in patients with prior cardiovascular event than those without. Conclusion. Systematic carotid atherosclerosis assessment by duplex ultrasonography in patients with type 2 diabetes and a contemporary cardiovascular prevention treatment does not offer additional information as to the risk of cardiovascular events. This trial is registered with ClinicalTrials.gov (ID: NCT02929355 ).